2004
DOI: 10.1095/biolreprod.103.020487
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrogen Peroxide in Sperm Capacitation and Acrosome Reaction1

Abstract: The generation of reactive oxygen species (ROS) has been implicated in the regulation of sperm capacitation and acrosome reaction; however, the mechanisms underlying this regulation remain unclear. To examine the cellular processes involved, we studied the effect of different concentrations of hydrogen peroxide (H(2)O(2)) on protein tyrosine phosphorylation under various conditions. Treatment of spermatozoa with H(2)O(2) in medium without heparin caused a time- and dose-dependent increase in protein tyrosine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
115
0
12

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(140 citation statements)
references
References 34 publications
7
115
0
12
Order By: Relevance
“…This process is associated with an increase in tyrosine phosphorylation, and it has been shown that the amount and banding pattern of tyrosine phosphorylation by adding exogenous H 2 O 2 was similar to that observed during endogenous ROS production, providing evidence that H 2 O 2 may be responsible for the enhancement of capacitation [32,57,58]. This hypothesis was further confirmed by Rivlin et al [59] who showed that catalase decreased, while H 2 O 2 increased the tyrosine phosphorylation in a dose-dependent manner, thereby solidifying the involvement of H 2 O 2 in the process of capacitation.…”
Section: Capacitationsupporting
confidence: 53%
See 3 more Smart Citations
“…This process is associated with an increase in tyrosine phosphorylation, and it has been shown that the amount and banding pattern of tyrosine phosphorylation by adding exogenous H 2 O 2 was similar to that observed during endogenous ROS production, providing evidence that H 2 O 2 may be responsible for the enhancement of capacitation [32,57,58]. This hypothesis was further confirmed by Rivlin et al [59] who showed that catalase decreased, while H 2 O 2 increased the tyrosine phosphorylation in a dose-dependent manner, thereby solidifying the involvement of H 2 O 2 in the process of capacitation.…”
Section: Capacitationsupporting
confidence: 53%
“…Both O 2 •− and H 2 O 2 may stimulate different molecules in the biochemical pathways, and depending on the in vitro method used to induce capacitation, specific ROS involved may therefore differ. Several studies have confirmed the lack of molecular specificity in the activation of capacitation and tyrosine phosphorylation, as both SOD and catalase have been shown to negate the positive effect exogenously induced capacitation and hyperactivation [59].…”
Section: Capacitationmentioning
confidence: 93%
See 2 more Smart Citations
“…On the other hand, some evidence exists demonstrating that ROS are important to spermatozoa in regulating every aspect of sperm function examined, including their movement characteristics, capacitation, sperm-zona interaction, acrosome reaction, and sperm-oocyte fusion (Baker & Aitken 2004, Rivlin et al 2004. Some studies have also documented that the addition of natural antioxidants to oocyte maturation medium failed to modify the percentage of bovine embryos produced in vitro (Blondin et al 1997) or even diminished the rate of embryo production (Dalvit et al 2005b).…”
Section: Introductionmentioning
confidence: 99%